OPTIMALISASI MEDIA DIGITAL PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH DASAR: (Studi kasus di SD Negeri 3 Pajaran) - Rohmatul Ummah; Muhammad Odik Afifin (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2025)
The advancement or information tecnology has brought significant changes in education, including in the teaching of Islamic Religious Education (PAI). Digital media has become a strategic tool for conveying religious values in a contextual and relevant manner to the lives of students. This study aims to analyze the utilization of digital media in PAI teaching at SD Negeri 3 Pajaran, identify implementation challenges, and formulate optimization strategies. This research employs a qualitative approach with a case study method. Data were collected through obsevasition, in-depth interviews, and document analysis. Findings indicate that the application of digital media, such as educational videos and online quizzes, can enhance students’ enthusiasm and understanding. Howevwr, the implementation of digital media still faces challenges, including limited technological devicas and inadequate insfrastructure support. This study recommends strengthening technological infrastructure, providing engaging digital learning materials, offering technical training for educators, and integrating hybrid learning methods to address these challenges. It is expected that optimizing digital media can improve the quality of PAI teaching and provide students with a more interactive and meaningful learning experience.